2021
DOI: 10.1177/0956462420987422
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperkalaemia due to a potential drug–drug interaction between eplerenone and antiretrovirals in a HIV-positive patient after a myocardial infarction

Abstract: We present a case of a 48-year-old white HIV-1 positive man who presented an acute myocardial infarction. The patient was on ART for the last ten years with emtricitabine/tenofovir and ritonavir-boosted fosamprenavir. Eplerenone 25 mg/day was also initiated due to a left ventricular dysfunction. A week after discharge a routine laboratory examination revealed severe hyperkalaemia. Due to suspicion of a potential drug–drug interaction, both eplerenone and ARVs were interrupted. Despite daily treatment for hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, clinical evidence of these drugÀdrug interactions has not been elucidated. Ezequiel et al [21] showed that a life-threatening hyperkalemic event resulted from a drug-drug interaction between eplerenone and ritonavir, a strong CYP3A4 inhibitor, in a patient infected with the human immunodeficiency virus. Clarithromycin also has a potent inhibition profile for CYP3A4 [12] and may interact with eplerenone and esaxerenone.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical evidence of these drugÀdrug interactions has not been elucidated. Ezequiel et al [21] showed that a life-threatening hyperkalemic event resulted from a drug-drug interaction between eplerenone and ritonavir, a strong CYP3A4 inhibitor, in a patient infected with the human immunodeficiency virus. Clarithromycin also has a potent inhibition profile for CYP3A4 [12] and may interact with eplerenone and esaxerenone.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently administration of eplerenone with protease inhibitors may cause a fourfold hike in the area under the curve (AUC) of eplerenone, which translates into the delayed clearance of the drug from the body (Talasaz et al 2020). Delayed clearance of eplerenone due to the said interaction leads to an increased risk of side effects, primarily hyperkalemia (Cordova et al 2021). Alternatively, the use of spironolactone is recommended in COVID-19 patients on protease inhibitors.…”
Section: Heart Failurementioning
confidence: 99%